The Effect of Entrepreneurial Orientation and Brand Orientation on SME Internalization and Performance: A Conceptual Framework - Mudalige, Darshana Mahilal; Ismail, Noor Azizi; Dassanayake, S.W.S.B (UUM Press, 2014)
This paper presents a framework for determining the relationships between entrepreneurial orientation and brand orientation on internationalization and performance of SMEs with the moderating effect of industry context and organizational learning. In review of the current literature, it was found that the complex investigation of SME performance involving the above variables has not been studied. Few and fragmentary studies have been conducted involving the variables yet they do not warrant us a broader generalization. Brand orientation has not been studied in association of SME internationalization so far. Studies involving entrepreneurial orientation and SME internationalization have been confronted with mixed results indicating the presence of a moderator/s in the relationship. Industry context is hypothesized as the as the moderator in this framework. The inability of the gradualist and non-gradualist models to explain the SME internationalization fully compels us to explore whether the above models are suited to explain the internationalization of SMEs in a particular industry. The mixed results of internationalization and performance can be attributed to the fact that the moderating effect of organizational learning has been ignored. According to gradualist theories, firm internationalization is based on “experimental knowledge”. Hence the ability of the organization to learn moderates the success of international endeavor. Furthermore, previous researchers have concentrated on entrepreneur orientation of founder or top managers as a predictor of internationalization. This framework identifies the middle managers’ perception of the internal environment for corporate entrepreneurship as an important predictor of performance especially in collectivist countries. This framework also proposes to extend the study to test non-financial aspects of firm performance as a result of internationalization which has gained surprisingly little attention. Therefore, to fill this research gap in research literature, a conceptual framework and hypotheses are developed.